The Spirit of the Book of Revelation. By Robby Waddell - Boxall, Ian (The journal of theological studies, 2008)
The ambiguity of this book's title is no doubt deliberate, and certainly effective. Robby Waddell's monograph, based on his Sheffield Ph.D. thesis, is no straightforward analysis of the Apocalypse's pneumatology, although the place of the Spirit in Revelation certainly provides its focus. Rather, it offers a reading of Revelation, and the role of the Spirit within it, which seeks to integrate recent scholarship on Revelation, literary theory (notably the intertextuality of Julia Kristeva), and Waddell's own religious context of Pentecostalism., Waddell acknowledges the paucity of scholarly treatment of the Spirit in Revelation, and seeks to redress the balance.